Human Rickettsia felis Infection, Canary Islands, Spain - Pérez-Arellano, Jose-Luis (Centers for Disease Control and Prevention, 2005)
We report the first cases of human infection by Rickettsia felis in the Canary Islands. Antibodies against R. felis were found in 5 adsorbed serum samples from 44 patients with clinically suspected rickettsiosis by Western blot serology. Fleas from 1 patient's dog were positive for R. felis by polymerase chain reaction.